Social Media Advertising and Electronic Word of Mouth as Determinants of Consumer Trust in the Pertamina Brand - Saputra, Muhammad Ragaswara; Yuliana, Lingga (Universitas Islam Kadiri, 2026)
This study empirically examines the influence of Social Media Advertising and Electronic Word of Mouth on Brand Trust among Pertamina consumers. The transformation of marketing communication in the digital era has shifted from traditional, one-way corporate messaging toward participatory and community-driven interactions. Digitally transmitted consumer opinions, experiences, and perceptions through eWOM have a substantial potential to shape public trust, emphasizing the relevance and urgency of this research. From a managerial perspective, the findings provide actionable insights for Pertamina in designing more effective digital communication strategies, recognizing that consumers are central actors in the dissemination and co-creation of brand meaning. A quantitative research design employing purposive sampling was adopted, and data were collected from 153 respondents residing in the Greater Jakarta area who had been exposed to Pertamina’s social media advertisements. The survey was administered online in October 2025, and the data were analyzed using the Partial Least Squares technique with SmartPLS version 4.1.0.0. The empirical results reveal that both social media advertising and eWOM exert a positive and significant effect on brand trust. These findings underscore the strategic importance of informative digital communication and constructive user engagement in fostering consumer trust toward the Pertamina brand. Managerial implications highlight the need to strengthen the credibility of advertising messages and actively manage eWOM to sustain brand reputation, trust, and long-term loyalty.